2018
DOI: 10.15282/jmes.12.1.2018.13.0307
|View full text |Cite
|
Sign up to set email alerts
|

Modified Weibull analysis on banana fiber strength prediction

Abstract: Nowadays, the world is facing a crisis in regards to renewable resources and rising carbon footprint. In the microscopic scale of engineering, this is where natural fibers come into play. Natural fibers comprise of considerable advantages that include being lightweight, inexpensive and renewable in comparison to their synthetic counterparts. The fibers are being used as reinforcement in composite matrices, including hybrid composites. The main issue with natural fibers is the high disparity of its mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…The following list is only a small fraction of what can now be found in the literature about the application of the Weibull distribution. Nevertheless, it illustrates well the versatility of this distribution, as well as the fact that to this day it is very often used to model such phenomena as: steel yield point, steel fatigue life [ 44 ], glass breaking strength [ 48 ], pitting corrosion of pipes [ 49 ], adhesion wear of metals [ 50 ], failure rate of carbon fibre composites [ 51 ], failure rate of coatings [ 52 ], failure rate of brittle materials [ 53 ], failure rate of composite materials [ 54 ], wear of concrete elements [ 55 ], fatigue life of aluminium alloys with high entropy [ 56 ], fatigue life of Al-Si castings [ 57 ], modelling of the power curve of a wind turbine [ 58 ], strength of materials using banana fibre [ 59 ], strength of polyethylene terephthalate fibres [ 60 ], and failure rate of joints under shear [ 61 ]. The Weibull distribution is also widely used to model the coalescence process of foams and emulsions, which was very well presented in the review article by Suja et al [ 62 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The following list is only a small fraction of what can now be found in the literature about the application of the Weibull distribution. Nevertheless, it illustrates well the versatility of this distribution, as well as the fact that to this day it is very often used to model such phenomena as: steel yield point, steel fatigue life [ 44 ], glass breaking strength [ 48 ], pitting corrosion of pipes [ 49 ], adhesion wear of metals [ 50 ], failure rate of carbon fibre composites [ 51 ], failure rate of coatings [ 52 ], failure rate of brittle materials [ 53 ], failure rate of composite materials [ 54 ], wear of concrete elements [ 55 ], fatigue life of aluminium alloys with high entropy [ 56 ], fatigue life of Al-Si castings [ 57 ], modelling of the power curve of a wind turbine [ 58 ], strength of materials using banana fibre [ 59 ], strength of polyethylene terephthalate fibres [ 60 ], and failure rate of joints under shear [ 61 ]. The Weibull distribution is also widely used to model the coalescence process of foams and emulsions, which was very well presented in the review article by Suja et al [ 62 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Fiber flaws or morphological defects, which can be built-in or induced during processing, serve as initiation sites of fiber failure. The strength of natural fibers exhibits a substantial scatter on diameter and dependence on fiber length [23][24][25]. In the study of Guo et al [25], the strength of short (10 mm) palm fibers is 20% higher than that of long (40 mm) fibers.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Guo et al [25], the strength of short (10 mm) palm fibers is 20% higher than that of long (40 mm) fibers. Sia et al [23] reported strength variations up to 16% for banana fibers of different lengths. Parlato et al [13] studied low-quality wool of a Sicilian sheep breed and reported on strength decrease within the fiber diameter: from 200 MPa for 50 µm fibers down to 50 MPa for 90 µm fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, the opportunity of employing a small wind turbines in Bali to harvest wind source is inspected theoretically and by simulation using Q-blade for the design and Weibull distribution through finding the probability of the wind speed, maximum power produced based on the probability, and the availability of the wind energy each of region in Bali. In the last decade, some investigator studied the wind power potential of some sites and it's wind characteristics in desert regions of Bali island and has been achieved with a few articles [3], [7], [8]- [18]. The objective is to mapping wind energy potential in the region of Bali and to determine the source of wind energy to possibility install the small wind turbines.…”
Section: Introductionmentioning
confidence: 99%